Bahaya Riba dalam Perspektif Hadis - HamdIah Latif (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2020)
This article aims to discuss the purpose of riba (usury) prohibition within The Prophet Tradition perspective. As it is known undoubtfully, the terminology of riba (usury) is forbidden not only in Islam as a religion but also in Jew as well as Christian. In Al-Qur’an itself, the prohibition of riba has gradually been prohibited, at least through four passages that are found in four disparate surahs in which riba (usury) at last is forbidden and condemned; even it is also considered as a great sin. By using bibliography studies, this article would like to dig and elaborate on some of the Prophet hadith regarding the prohibition of riba and its impact within society. It is believed that riba is a great sin in Islam because it leads to social jealousy and injustice. Therefore the tradition of riba is aiming at promoting gracious, wisdom, a mutual benefit that can realize a more just economic system that is based on Islamic ethics to perform justice and prosperity.AbstrakArtikel ini ingin membahas tujuan dari pelarangan riba dalam perspektif hadis. Tidak diragukan lagi, istilah riba sebenarnya dilarang dalam semua agama samawi, baik Yahudi, Kristen maupun Islam. Di dalam Al-Qur'an sendiri, pelarangan riba memiliki empat ayat yang ditemukan pada empat surat berbeda, di mana riba jelas-jelas dikutuk dan dilarang, bahkan riba dinyatakan pula sebagai dosa yang sangat serius. Dengan menggunakan studi literatur, artikel ini ingin menggali dan mendalami beberapa hadis tentang larangan riba dan dampaknya di masyarakat. Dikatakan bahwa riba adalah dosa dalam Islam, karena mengarah pada kehancuran, sedangkan sedekah mengarah kepada pertumbuhan. Oleh karena itu, penghapusan riba sebenarnya bertujuan untuk memajukan sistem ekonomi yang merahmati, lebih berkeadilan, hubungan sosial yang lebih berimbang serta nilai-nilai etika yang sejalan dengan ajaran Islam.